Culture, myths and panic: Three decades and beyond with an HIV/AIDS epidemic in Zimbabwe. Issue 2 (1st February 2018) - Chingwaru, Walter; Vidmar, Jerneja
ABSTRACT: Zimbabwe is going through a generalised acquired immunodeficiency syndrome (AIDS) epidemic. The first five years of the epidemic (1985-1990) were characterised by lack of medicines against human immunodeficiency virus (HIV), and an exponential increase in prevalence (65-fold) and incidence (13-fold), which were fuelled by high-risk sexual behaviour. The high HIV prevalence, mortality and stigma yielded great fear and panic in the population, which are thought to have led to confusion and hopelessness, and, in turn, increased risky sexual behaviour. The country's government and civil society embarked on HIV awareness campaigns that are claimed to have played a central role in slowing down the epidemic since the mid-2000s. HIV-related mortality then fell by 70% between 2003 and 2013, which is attributed to high uptake of antiretroviral therapy (ART) and prevention of mother-to-child transmission (95%) prophylaxis. However, the epidemic has been characterised by a low paediatric ART coverage (35% in 2011 to 46.12% in 2013). Year 2014 saw an increase in adolescent and young adult HIV prevalence, which may be signalling a rebound of the epidemic. A more holistic approach which deals with the epidemic in its socio-political context is required to effectively lower the country's HIV burden.